"Liquid-liquid-solid"-type superoleophobic surfaces to pattern polymeric semiconductors towards high-quality organic field-effect transistors - Wu, Yuchen (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.